A new sorbent of polypyrrole/Silica/Magnetite Nanoparticles for the extraction of sulfonamides from water samples - Thanyaporn Sukchuay (Prince of Songkla University, 2017)
Thesis (M.Sc, (Chemistry))--Prince of Songkla University, 2015